Molecular Diagnosis of Toxoplasma gondii and Neospora caninum in Brain Tissues of Some Wild Birds - Altug, Enes; Isler, Cafer Tayer; Orunc Kilinc, Ozlem; Muz, Mustafa Necati; Karakavuk, Muhammet (Kafkas Universitesi Veteriner Fakultesi Dergisi, 2015)
WOS: 000349190400005 There are limited molecular studies about Toxoplasma gondii and Neospora caninum which are economically important livestock protozoons in wild birds investigated by polymerase chain reaction (PCR) method. Molecular prevalance of both parasites in brain tissues of wild birds in Turkey is unknown. Prevalance of T. gondii was 7%, N. caninum was 14% and mix infection was found 4% in brain tissues of 101 wild birds under 20 species from two different regions of Turkey. The chi-square test has been applied to the acquired data. This is the first molecular biologic investigation for the aim of PCR diagnosis of T. gondii in brain tissues of Corvus corone, Melanitta fusca, Aquila heliaca, Aquila pomarina, Buteo rufinus, Accipiter nisus, Strix aluco and N. caninum in brain tissues of Larus genei, Corvus corone, Melanitta fusca, Anas clypeata, Perdix perdix, Aquila heliaca, Buteo rufinus in the world. This also is the first molecular diagnostic investigation of T. gondii and N. caninum in brain tissues of wild birds in Turkey.